2016
DOI: 10.1097/gme.0000000000000567
|View full text |Cite
|
Sign up to set email alerts
|

Compounded non-FDA–approved menopausal hormone therapy prescriptions have increased

Abstract: Objective:From a survey of compounding pharmacists, specific questions regarding compounded menopausal hormone therapy were used to estimate compounded hormone therapy (CHT) prescribing in the United States.Methods:A national online survey was conducted by Rose Research—a market research company consisting of 12,250 US pharmacists from independent community pharmacies (ICPs) and compounding pharmacies (CPs). Pharmacists who completed the survey and met the prespecified criteria were eligible. Data from the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…This report is the third in a series of surveys designed to elucidate the scope of the CHT market in the United States. 17 , 19 The first was a report using prescription claims for FDA-approved HT and US Census data to extrapolate data from surveys of consumers to estimate the number of women using CHT annually at up to 2.5 million, representing 28% to 68% of all HT prescriptions. 17 The second report, using a survey of pharmacists, National Community Pharmacists Association data, and IBISWorld data, concluded that approximately 26 to 33 million CHT prescriptions are filled annually at a cost of between $1.3 and $1.6 billion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report is the third in a series of surveys designed to elucidate the scope of the CHT market in the United States. 17 , 19 The first was a report using prescription claims for FDA-approved HT and US Census data to extrapolate data from surveys of consumers to estimate the number of women using CHT annually at up to 2.5 million, representing 28% to 68% of all HT prescriptions. 17 The second report, using a survey of pharmacists, National Community Pharmacists Association data, and IBISWorld data, concluded that approximately 26 to 33 million CHT prescriptions are filled annually at a cost of between $1.3 and $1.6 billion.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this survey was to assess physicians’ prescribing practices of HT, in particular CHT, among US physicians of different specialties. The survey of physicians reported here is the third in a series of three reports on the results of surveys of consumers, 17 compounding pharmacists, 19 and physicians, designed to gain a clearer picture of the size of the CHT market and the reasons behind its growth.…”
mentioning
confidence: 99%
“…Essa terapia foi amplamente utilizada entre as mulheres até 2002, mas as atitudes das mulheres e dos clínicos mudaram, consideravelmente, nos últimos anos. Estudos concluíram que os efeitos nocivos da TRH excedem os benefícios e o fato ocasionou uma diminuição das prescrições médicas, levando as mulheres a buscar terapias alternativas 14 .…”
Section: Terapia De Reposição Hormonal: Riscos E Benefíciosunclassified
“…After the Women's Health Initiative (WHI) trial identified potential risks with HT containing synthetic progestin [7], an increasing demand for bioidentical HT containing estradiol (E2) and progesterone (P4) was observed [8] as many women perceive bioidentical HT to be more 'natural' and safer [9][10][11][12]. Since no US Food and Drug Administration (FDA)approved bioidentical combination products were available at that time, many women opted to take unapproved, unregulated compounded HT (CHT; commonly advertised as bioidentical).…”
Section: Introductionmentioning
confidence: 99%
“…Since no US Food and Drug Administration (FDA)approved bioidentical combination products were available at that time, many women opted to take unapproved, unregulated compounded HT (CHT; commonly advertised as bioidentical). As of 2016, an estimated 33 million prescriptions were filled annually in the US for CHT [8]. However, due to the lack of quality control, unestablished safety and efficacy, and low level of regulatory oversight, medical societies [5,6] and the FDA [13] recommend against the use of CHT.…”
Section: Introductionmentioning
confidence: 99%